Tax Audit Management, Technology Integration and Performance of State Internal Revenue Service in Southwest, Nigeria: English - Olumoh, Yusuf Alabi; Sanni, Mubaraq (Yayasan Ilomata, 2024)
The State Internal Revenue Services in Southwest Nigeria struggle with tax compliance rates and revenue generation optimization due to inadequate audits and low technology adoption, which affects detection, evasion reduction, accountability, and transparency in tax administration. Therefore, this study investigated the impacts of tax audit management (TAM) and technology integration (TI) in improving the performance of SIRS in Southwest Nigeria. The study employed a cross-sectional quantitative survey research design, data were collected from 383 management personnel across various SIRS offices in South-West, Nigeria. PLS-SEM was employed to examine the impact of TAM and TI on SIRS performance. The findings indicate that TAM significantly enhances SIRS performance, with a coefficient of 0.440, a t-statistic of 2.736, and a p-value of 0.006, suggesting that effective tax audits boost revenue generation and reduce tax evasion. TI also positively influences SIRS performance, with a coefficient of 0.328, a t-statistic of 2.143, and a p-value of 0.032, emphasizing its role in streamlining tax processes and improving compliance. However, the combined interaction effect of TI and TAM on SIRS performance is not statistically significant, with a coefficient of -0.050, a t-statistic of 0.523, and a p-value of 0.601. This study concludes that both TAM and TI independently contribute to SIRS performance, their combined effect does not significantly enhance the operational efficiency of tax authorities. Based on these findings, the study recommends that SIRS in Southwest Nigeria should prioritize the adoption of comprehensive tax audit management strategies and leverage technology to automate and optimize tax processes.